Identification and molecular characterization of peroxiredoxin 6 from noble scallop Chlamys nobilis revealing its potent immune response and antioxidant property. Issue 100 (May 2020) - Cheng, Dewei; Zhang, Hongkuan; Liu, Hongxing; Zhang, Xinxu; Tan, Karsoon; Li, Shengkang; Ma, Hongyu; Zheng, Huaiping
Abstract: The 1-cyseine peroxiredoxin (Prx6) is an importantly antioxidant enzyme that protects cells from oxidative damage caused by excessive production of reactive oxygen species (ROS). In this study, we described the molecular characteristics of the noble scallop Chlamys nobilis peroxiredoxin 6 (designed as CnPrx6 ), immune responses and DNA protection activity of the recombinant protein. The complete ORF (696 bp) of CnPrx6 encoded a polypeptide (25.5 kDa) of 231 amino acids, harboring a conserved peroxidase catalytic center ( 41 PVCTTE 46 ) and the catalytic triads putatively involved in peroxidase and phospholipase A2 activities. The deduced amino acid sequence of CnPrx6 shared a relatively high amino acid sequence similarity (more than 50%). The qRT-PCR revealed that the CnPrx6 mRNA was constitutively expressed in all examined tissues, with the highest expression observed in adductor. Upon immunological challenge with Vibrio parahaemolyticus, lipopolysaccharides (LPS) and polyinosinic-polycytidylic acid (Poly I:C), the expression level of CnPrx6 mRNA was significantly up-regulated ( P  < 0.05). Furthermore, there was a significant difference ( P  < 0.05) in the expression level of CnPrx6 between golden and brown scallops. The purified recombinant CnPrx6 protein protected the supercoiled plasmid DNA from metal-catalyzed ROS damage. Taken together, these results indicated that the CnPrx6 may play an important role in modulating immune responses and minimizing DNA damage in noble scallop Chlamys nobilis . Highlights: Prx6 gene (designed as CnPrx6 ) was first time identified in the noble scallop Chlamys nobilis. CnPrx6 was involved in the immune response against pathogen infection. Different responses were existed between golden and brown scallop under immunity stress. Purified recombinant CnPrx6 protein can protect supercoiled plasmid DNA from damages.